The The Effectiveness of a Program Based on the Teaching of Affixes in Developing Morphological Awareness among the Students of the Faculty of Arts, Dhamar University - ALSAKKAF, AFAF; Al-Mekhlafi , Mohammad Abdu (International Journal of Language and Literary Studies, 2023)
This study aimed to investigate: a) To what extent the teaching of affixes affects in developing the students’ morphological awareness of English, b) If there are significant differences between the experimental group and the control group in the English morphological awareness. Due to the nature of the study, the researcher used quasi- experimental research. The instruments of data collection were morphological awareness tests which involve the tests of prefixes, suffixes, distributional and syntactic aspect. The study used means, standard deviation, paired sample t-test and an independent sample t- test. The program went through ten affixes sessions for two months and 15 days. The participants of this study were forty-two students. They were second-year students enrolled in the Bachelor of Arts at the University of Dhamar in Yemen in the academic year 2022 /2023. The findings revealed that the participants’ level of morphological awareness was highly developed and that there were statistically significant differences at the significance level (? 0.05) of the morphological awareness test as a whole, and for each of its four domains separately in favour of the students of the experimental group in the participants’ mean scores before and after using affixes program and between the experimental and control group in favour of the experimental group. It was observed that the program was very interesting and successful. Thus, it enabled students to identify and produce different word classes and have a lot of vocabularies which are necessary for EFL learners. They became perfect in the morphological awareness after the teaching of affixes.